The Influence of TikTok Live Streaming and EXO Brand Ambassador on Brand Awareness and Its Impact on Purchase Interest of Scarlett Generation Z Skincare in Semarang. - Sintaningrum, Picantia Bunga; Kurniawan, Rudi (Inovbiz: Jurnal Inovasi Bisnis, 2024)
The increasing market for the cosmetics industry brings hope for the development of the skincare industry Indonesia, one of which is Scarlett. This type of research uses descriptive research with a quantitative approach. The purpose of this research is to determine the influence of Live Streaming and Brand Ambassadors on Brand Awareness and its impact on Generation Z Scarlett Skincare Purchase Interest in Semarang City. The data analysis technique used is IBM SPSS AMOS 24 Graphics software. The results of this research show that Live Streaming has a significant effect on Brand Awareness, Brand Ambassador has a significant effect on Brand Awareness, Live Streaming has no significant effect on Purchase Interest, Brand Ambassador has no significant effect on Purchase Interest, and Brand Awareness has a significant effect on Purchase Interest.